2009
DOI: 10.1093/eurheartj/ehp008
|View full text |Cite
|
Sign up to set email alerts
|

The impact of valve surgery on short- and long-term mortality in left-sided infective endocarditis: do differences in methodological approaches explain previous conflicting results?

Abstract: Previous conflicting results appear to be related to differences in statistical methods. When using appropriate models, we found that VS was significantly associated with reduced long-term mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
89
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(100 citation statements)
references
References 31 publications
5
89
0
6
Order By: Relevance
“…Po incydencie neurologicznym często pojawiają się lub uzyskują dodatkowe znaczenie wskazania do leczenia operacyjnego, ale kwalifikując chorego do operacji należy wziąć pod uwagę proporcje między ryzykiem przedoperacyjnym a zakładanym rokowaniem pooperacyjnym. Nie jest możliwe prowadzenie badań randomizowanych, a badania kohortowe są obciążone błędami doboru grupy badanej, które tylko w części mogą być zrów-noważone metodami statystycznymi [115,[260][261][262]. Jednak po bezobjawowym zatorze mózgowym lub przemijającym epizodzie niedokrwienia mózgu ryzyko pooperacyjnego pogorszenia stanu neurologicznego jest niskie, dlatego w przypadku utrzymujących się wskazań należy bez opóźnień przeprowadzić zabieg operacyjny [105].…”
Section: Wskazania I Tryb Leczenia Operacyjnego W Celu Zapobiegania Zunclassified
“…Po incydencie neurologicznym często pojawiają się lub uzyskują dodatkowe znaczenie wskazania do leczenia operacyjnego, ale kwalifikując chorego do operacji należy wziąć pod uwagę proporcje między ryzykiem przedoperacyjnym a zakładanym rokowaniem pooperacyjnym. Nie jest możliwe prowadzenie badań randomizowanych, a badania kohortowe są obciążone błędami doboru grupy badanej, które tylko w części mogą być zrów-noważone metodami statystycznymi [115,[260][261][262]. Jednak po bezobjawowym zatorze mózgowym lub przemijającym epizodzie niedokrwienia mózgu ryzyko pooperacyjnego pogorszenia stanu neurologicznego jest niskie, dlatego w przypadku utrzymujących się wskazań należy bez opóźnień przeprowadzić zabieg operacyjny [105].…”
Section: Wskazania I Tryb Leczenia Operacyjnego W Celu Zapobiegania Zunclassified
“…23 Among patients with complications that require emergent intervention, the optimal timing for surgery remains controversial. 45 Early surgery however, has been shown to decrease the rate of embolic events, 46 in-hospital, 47 and 6-month mortality. 48 Two studies in our review reported on the timing of surgery.…”
Section: Surgical Managementmentioning
confidence: 99%
“…15 However, these studies had substantial biases and lacked methodologic or statistical rigour. Although it is not established Practice that early surgery is superior for all patients, emerging studies suggest that earlier intervention may reduce the occurrence of embolic events and death.…”
Section: Timingmentioning
confidence: 99%